Les Stratégies D’enseignement/ Apprentissage du FOU à L’université Algérienne: Impact et Enjeux - Hadbi, Anissa (المركز الجامعي مغنية - معهد الآداب واللغات, 2021)
The teaching of scientific subjects at the Algerian university is carried out, for the most part, in French. This creates a lot of difficulties for the majority of students during their university studies given their level in French. Hence the interest shown by didacticians in this problem. Our article is a reflection on the teaching of FOU in the Department of Natural and Life Sciences, using ICT from both a theoretical and practical point of view. Therefore, we will focus our research on the types of difficulties encountered by students and the role of ICT in the teaching of scientific fields.
Keywords: التعليم العالي -- تكنولوجيا المعلومات -- طرق التدريس -- الجزائر